2006
DOI: 10.1152/ajpregu.00366.2005
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of the kinetics of cardiac output, systemic O2 delivery, and lung O2 uptake at exercise onset in men

Abstract: Simultaneous determination of the kinetics of cardiac output, systemic O 2 delivery, and lung O2 uptake at exercise onset in men. Am J Physiol Regul Integr Comp Physiol 290: R1071-R1079, 2006. First published October 20, 2005 doi:10.1152/ajpregu.00366.2005.-We tested whether the kinetics of systemic O 2 delivery (Q aO2) at exercise start was faster than that of lung O 2 uptake (V O2), being dictated by that of cardiac output (Q ), and whether changes in Q would explain the postulated rapid phase of the V O2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
93
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 56 publications
19
93
4
Order By: Relevance
“…2) lends further credence to earlier studies investigating the haemodynamic response to rest-to-exercise transitions. In these studies, it was shown that a steady state for cardiac output is attained between 30 (Lador et al 2006(Lador et al , 2008 and 60 s (De Cort et al 1991). Also, Davies et al (1972) found a rapid adjustment of cardiac output after increasing power (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2) lends further credence to earlier studies investigating the haemodynamic response to rest-to-exercise transitions. In these studies, it was shown that a steady state for cardiac output is attained between 30 (Lador et al 2006(Lador et al , 2008 and 60 s (De Cort et al 1991). Also, Davies et al (1972) found a rapid adjustment of cardiac output after increasing power (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence for quick adjustments of cardiac output to increased power comes from the examination of haemodynamics during rest-to-exercise transitions in healthy participants by determining cardiac function on a beat-by-beat basis, using Doppler ultrasound (De Cort et al 1991) or the model flow method (Lador et al 2006(Lador et al , 2008. These studies showed that when increasing power from rest to 50, 80, or 100 W (i.e., "rest-to-exercise" transitions), a steady state for cardiac output is quickly reached (e.g., within the first minute).…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that the correction factor is independent of exercise intensity and thus of the ongoing blood flow and TPR. As a consequence, the method can conveniently be used for the analysis of dynamic states (Lador et al, 2006).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…However, under nonsteady state conditions, VO 2p is unlikely to provide a reliable estimation of muscle oxygen consumption because of a potential dissociation between them at exercise onset Lador et al 2006). To provide additional insight into muscle oxidative function, measurements can be made with respect to blood-tissue oxygen transfer directly from skeletal muscle .…”
Section: Introductionmentioning
confidence: 99%